Analysis of acoustic patterns in honey bees- An investigation - Bijoyaa Mohapatra; Nisha Sudhi; Liveem M Tharakan; Sri Pallavi M; Anil Kumar; Yeshoda K (Journal of All India Institute of Speech and Hearing, 2010)
‘Communication’ is believed to be the exchange of information between two partners. The broad field of animal communication encompasses most of the issues in ethology. Honey bee communication has been of special interest to ethologists. The purpose of this study is to determine the acoustic characteristics of the honey bees buzz in a species of Apis dorsata dorsata in natural and induced environmental conditions. The results revealed that change in the external conditions led to characteristic changes in the acoustic properties of the sounds produced by the honey bees. The mean fundamental frequency of bee buzz increased in the induced conditions compared to natural condition whereas amplitude variations were not consistent across conditions. These variations in communication patterns in honey bees across different conditions (pleasant or threatful situations) gives us good reason to call the communication pattern in honey bees as ‘language.